Pengaruh Model Pembelajaran Project Based Learning (PjBL) Terintegrasi STEM Pada Mata Pelajaran Fisika Untuk Meningkatkan Kemampuan Berfikir Kreatif Peserta Didik SMA TGH Umar Kelayu Tahun Ajaran 2021/2022 - Moammar Qadafi; Andriyani Hastuti; Jamaluddin (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Project based learning is a learning model or design that contributes to student learning activities so that it can increase creativity, motivation and interest, responsibility, communication, social skills, cooperation and problem solving abilities (Shin et all 2018:97). The project based learning model in this study was integrated with STEM to improve students' creative thinking skills. Based on the results of the study, it was obtained in the experimental class that students' critical thinking skills were higher than in the classical control class, namely 75.33 and 65.29. So based on these data it can be concluded that the STEM integrated project based learning model can improve students' creative thinking skills